1-a26=0

To remove the radical on the left side of the equation, raise both sides of the equation to the power of 6.

1-a266=06

Multiply the exponents in ((1-a2)16)6.

Apply the power rule and multiply exponents, (am)n=amn.

(1-a2)16⋅6=06

Cancel the common factor of 6.

Cancel the common factor.

(1-a2)16⋅6=06

Rewrite the expression.

(1-a2)1=06

(1-a2)1=06

(1-a2)1=06

Simplify.

1-a2=06

Raising 0 to any positive power yields 0.

1-a2=0

1-a2=0

Subtract 1 from both sides of the equation.

-a2=-1

Multiply each term in -a2=-1 by -1

Multiply each term in -a2=-1 by -1.

(-a2)⋅-1=(-1)⋅-1

Multiply (-a2)⋅-1.

Multiply -1 by -1.

1a2=(-1)⋅-1

Multiply a2 by 1.

a2=(-1)⋅-1

a2=(-1)⋅-1

Multiply -1 by -1.

a2=1

a2=1

Take the square root of both sides of the equation to eliminate the exponent on the left side.

a=±1

The complete solution is the result of both the positive and negative portions of the solution.

Any root of 1 is 1.

a=±1

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

a=1

Next, use the negative value of the ± to find the second solution.

a=-1

The complete solution is the result of both the positive and negative portions of the solution.

a=1,-1

a=1,-1

a=1,-1

a=1,-1

Solve for a sixth root of 1-a^2=0